The effects of vitamin D levels on physical, mental health, and sleep quality in adults: a comprehensive investigation - Anurag Kumar Singh; Sachin Kumar; Shivang Mishra; Sumit Rajotiya; Sourav Debnath; Preeti Raj; Hemant Bareth; Mahaveer Singh; Deepak Nathiya; Deepak Nathiya; Deepak Nathiya; Balvir Singh Tomar; et al. (Frontiers in Nutrition)
BackgroundVitamin D, essential hormone for endocrine, autocrine, and paracrine functions. A billion people are deficient globally which contributing to numerous health issues. This study explores the link between vitamin D levels and sleep quality, impacting mental and physical health in adults.MethodsThis prospective cross-sectional study was conducted at Nims Hospital, Jaipur, involving 484 adults’ participants. Blood samples were collected for serum 25(OH) D measurements. Data were gathered using the SF-36 and ISI questionnaires to assess health and sleep quality.ResultsHigher vitamin D levels were strongly linked to better physical health, including physical function (r = 0.642, p < 0.001), general health (r = 0.560, p < 0.001), and PCS score (r = 0.441, p < 0.001). Vitamin D also positively impacted social functioning (r = 0.096, p = 0.035) and was negatively related to ISI scores (r = −0.112, p = 0.014).ConclusionThe study highlights a strong link between higher vitamin D levels and improved physical and mental health, with significant negative correlation to ISI scores. This underscores the importance of adequate vitamin D for overall well-being. The findings call for urgent measures to address vitamin D deficiency and further research into its health impacts.